Subnanomolar antisense activity of phosphonate-peptide nucleic acid (PNA) conjugates delivered by cationic lipids to HeLa cells - Shiraishi, Takehiko (Oxford University Press, 2008)
In the search of facile and efficient methods for cellular delivery of peptide nucleic acids (PNA), we have synthesized PNAs conjugated to oligophosphonates via phosphonate glutamine and bis-phosphonate lysine amino acid derivatives thereby introducing up to twelve phosphonate moieties into a PNA oligomer. This modification of the PNA does not interfere with the nucleic acid target binding affinity based on thermal stability of the PNA/RNA duplexes. When delivered to cultured HeLa pLuc705 cells by Lipofectamine, the PNAs showed dose-dependent nuclear antisense activity in the nanomolar range as inferred from induced luciferase activity as a consequence of pre-mRNA splicing correction by the antisense-PNA. Antisense activity depended on the number of phosphonate moieties and the most potent hexa-bis-phosphonate-PNA showed at least 20-fold higher activity than that of an optimized PNA/DNA hetero-duplex. These results indicate that conjugation of phosphonate moieties to the PNA can dramatically improve cellular delivery mediated by cationic lipids without affecting on the binding affinity and sequence discrimination ability, exhibiting EC(50) values down to one nanomolar. Thus the intracellular efficacy of PNA oligomers rival that of siRNA and the results therefore emphasize that provided sufficient in vivo bioavailability of PNA can be achieved these molecules may be developed into potent gene therapeutic drugs.